Análisis comparativo entre los delitos de enriquecimiento ilícito y enriquecimiento no justificado en la legislación ecuatoriana - Ocles Insuasti, Amanda Julissa (2024)
The objetive of this research is to make a comparative analysis between two criminal types since it is necessary to investigate in depth the problem of illegally enriching oneself, both concepts seek to combat corruption, although with slightly different approaches. The general objective of this research work was to compare the crimes of illicit enrichment and unjustified enrichment in Ecuadorian legislation, through the analysis of the typification in the Organic Integral Penal Code, their similarities and differences, in addition to the study of emblematic and notable cases for the Ecuadorian society, to understand their impact on the effectiveness of the prosecution of corruption. The research was developed from a qualitative approach with a descriptive scope because it analyzes the most important and relevant aspects of the crimes and their increasing incidence. The analytical method was applied to analyze the criminal types described in the norms studied\; likewise, the comparative legal method was used to compare the various elements that make up both crimes, to contrast both legal realities. In addition, the Normative method was used, as it is the appropriate method to analyze the legal norms that enshrine the criminal types indicated. From the information obtained through the techniques and instruments used, it could be evidenced that there is a progressive increase in the increase of assets of public officials and individuals in an illegal and unjustified manner\; affecting the good development of public administration as a protected legal good and society, which makes this work relevant. It was concluded that the sentences issued for cases of enrichment are not fair and equitable because of the damage caused and there is also interference in the judiciary causing economic damage to the country and society.